The Big society's new public sphere? faith after community cohesion - Ahmad, Khairil Izamin (2011)
This paper seeks to critically examine contemporary debates regarding the position of religion and religious citizens in the public spheres of contemporary liberal democracies. This will be done by exploring if and how the role of faith and faith communities will be reconfigured under the Conservative-Liberal Democrat coalition’s Big Society project in the UK, in contrast to New Labour’s community cohesion initiative, vis-à-vis the former’s call for the reaffirmation of ‘British values’ at the national level. Seen from the lenses of post-Marxist discourse analysis, particularly through the deployment of the logics of critical explanation, this paper finds few points of divergence in between the approaches of New Labour and the coalition government. While faith and faith communities are reaffirmed as vital ‘social capitals’ in local level policies, both attempt to delimit the public potentials of religion and religious citizens by way of defining them as democratic positions and citizens that are at odds with the ‘mainstream’ citizen. This paper explores the possibilities for an alternative vision of a deeply and multidimensionally pluralistic public culture as a normative response to the failings of the present secular liberal configuration.